Leadership and Ideological Bond: PPP and Internal Fragmentation in Indonesia - Noor, Firman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2016)
During 2014-2016, the United Development Party (PPP) experienced the most severe and prolonged internal fragmentation in its history. Since the beginning of 2014, the emergence of the twin Board of the Central Committee cemented the fragmentation that had occurred. Some people relate this phenomenon to the interests of the elites. However, the interest of the elites itself is something inevitable and in many cases is not necessarily the cause for prolonged fragmentation. The aim of this article, therefore, is to explain the factors that lead to the internal fragmentation. This article regards three main root-causes of the problem, namely (1) weak leadership, in particular the absence of a strong patron, which facilitates cadres’ unrestricted freedom of action and makes them unable to maintain the Party unity, (2) the lack of an ideological bond that leads to the growth of exclusive-pragmatism, and (3) external factors, namely the government and coalition partners that are eager to preserve each conflicting group’s position.DOI: 10.15408/sdi.v23i1.2808